LM and SEM study on the swordfish (Xiphias gladius) tongue. Issue 6 (December 2017) - Abbate, Francesco; Guerrera, Maria Cristina; Cavallaro, Mauro; Montalbano, Giuseppe; Germanà, Antonino; Levanti, Maria
Highlights: The anatomical characteristics of the swordfish tongue, especially its dorsal surface are showed. The tongue has a triangular shape and can be divided in an apex, a body and a root. Several small denticles and filiform papillae on the latero-ventral body areas are present. A squamous stratified epithelium, becoming simple cuboidal around the denticles can be observed. Abstract: Swordfish (Xiphias gladius L. 1758) is a predatory and migratory fish. Its characteristic feature is a flat and sharp upper jaw forming a "sword". The adaptation of vertebrates, including fish, to their environment is strictly related to the capacity of feeding and is carried out by often severe modifications of the anatomy of the buccal cavity, especially of the tongue. The aim of this study is, using light and scanning electron microscopy and considering that no data are so far available about the morphology of the tongue in this species, to analyse the anatomical characteristics of the tongue, especially its dorsal surface. The tongue shows a triangular shape and an apex, a body and a root. By SEM the presence of several small denticles and filiform papillae on the latero-ventral body was demonstrated while no taste buds or other sensitive structures are observed. LM shows a squamous stratified epithelium, becoming simple cuboidal around the denticles. Therefore this study could add further data to the knowledges of the fish oral cavity morphology supporting the hypothesis that the modifications and evolution of the tongue anatomy are, also in fish, related to the environment and especially to the feeding habits.